Preliminary transcriptomic analyses reveal in vitro and in planta overexpression of various bacteriocins in Xylella fastidiosa - Amoia, Serafina Serena; Saponari, Maria; Saldarelli, Pasquale; Ligorio, Angela Maria; Grosso, Carmine Del; Loconsole, Giuliana; D’Attoma, Giusy; Boscia, Donato; Giampetruzzi, Annalisa (Frontiers in Microbiology, 2025)
IntroductionXylella fastidiosa is a phytopathogenic bacterium of worldwide importance causing detrimental diseases in several crops. Recent reports from European and Mediterranean countries raised great concerns and have given impetus to new studies investigating both the pathogenicity of the newly emerged strains and the susceptibility and vulnerability of Mediterranean agroecosystems, with the outbreak in olive trees in southern Italy being the most investigated new pathosystem. The complexity of this pathogen makes difficult to understand its interaction mechanisms with host plants and plant microbial communities.Materials and methodsIn this study, we performed a pilot dual RNA-seq analysis on a diseased olive tree infected by Xylella fastidiosa subspecies pauca, to gather information about bacterial infection dynamics and reciprocal interactions between plant host and the bacterium. Adopting a mRNA enrichment protocol allowed to better probe bacterial sequences by increasing the resolution of differential gene expressions.ResultsThe overexpression of a bacteriocin (cvaC-1), as the major result gained by the transcriptomic analysis, led us to validate its potential application as a marker of Xylella fastidiosa multiplication in olive, citrus and periwinkle artificially inoculated plants. Transcriptomic analysis of in vitro cultured strains of Xylella fastidiosa subspecies pauca, while confirming that bacteriocin-related genes are the most abundant transcripts, unraveled strain differences in the cvaC-1 and cvaC-2 ratio.DiscussionOur findings suggest that the cvaC-1-related transcript can be employed in RT-qPCR/RT-PCR to improve the detectability of actively growing Xylella fastidiosa cells in vitro and in host’s xylem vessels. Indeed, being the most expressed component of bacterial weapons, novel studies focusing on its functions and role in the bacterial pathogenic life cycle should be envisioned.